Golgi protein 73: charting new territories in diagnosing significant fibrosis in MASLD: a prospective cross-sectional study - Hong, Shan; Liu, Ziyu; Li, Ping; Zhang, Jing; Wei, Hongshan (Frontiers in Endocrinology, 2025)
ObjectivesTo explore the correlation between serum Golgi protein 73 (GP73) levels and the degree of fibrosis in Metabolic dysfunction associated steatotic liver disease (MASLD); to establish a non-invasive diagnostic algorithm based on serum GP73 and liver elasticity.MethodsThis is a prospective cross-sectional study, including 228 patients diagnosed with MASLD from May 2018 to January 2024 at two tertiary hospitals. Clinical data and hepatic pathological features and the correlation between serum GP73 and liver fibrosis were assessed. A new algorithm was conducted after logistic regression. Receiver Operating Characteristic (ROC) curve was used to compare its diagnostic performance with traditional models.ResultsSignificant fibrosis was diagnosed in 37.2% (85/228) patients. Serum GP73 levels were markedly higher in patients with significant fibrosis than in those without (128 ng/mL v.s 46 ng/mL, p< 0.001). Serum GP73 levels independently predicted significant liver fibrosis (adjusted odds ratio, aOR 1.028, p< 0.001). A new algorithm based on GP73 was developed with a higher area under ROC (AUC) of 0.840 than that of Fibrosis index-4 (p< 0.001).ConclusionsSerum GP73 is an independent risk factor for significant liver fibrosis in MASLD, and the GFA (GP73-Fibroscan-Age) model has good diagnostic efficacy for significant liver fibrosis.